The Role of Batik Museum as The Effort in Increasing The Cultural Awareness of Junior High School Students in Pekalongan - Setiawan, Wawan; Pramono, Suwito Eko; Sanjoto, Tjaturahono Budi (JESS (Journal of Educational Social Studies), 2018)
Pekalongan City is one of a city that has a local cultural heritage which is batik. It makes a necessity to continue preserve batik so that it will keep abreast of the times. Hence, it is needed the role of batik museum in the effort to increase the cultural awareness especially for junior high school students in Pekalongan City. The aim of this research is to know the role of Batik Museum of Pekalongan as the effort to increase the cultural awareness toward junior high school students in Pekalongan City by looking at the condition of students’ cultural awareness in advance, so as to mention any constraints that appear related to the role of batik museum. Method used in this research was qualitative research. Methods of collecting data used in this research by using depth interview, observation, and documents study. The research result shows that the level of cultural awareness toward students in Pekalongan was at the level of cultural knowledge. And the main aspect that directly affect related to the role of the museum in the effort of increasing cultural awareness toward junior high school students in Pekalongan is Goal Attainment aspect. This aspect will directly determine whether the the purpose of batik museum to increase knowledge and education (cultural awareness) towards students can run well or not.